Characteristics of Biochars from Plant Biomass Wastes at Low-Temperature Pyrolysis - Liska Mutiara Septiana; Gunawan Djajakirana; Darmawan Darmawan (Universitas Sebelas Maret, 2018)
The effects of biochar as soil ameliorants depend on their characteristics that are influenced by the variation in biomass origin and pyrolysis process. In this context, the objective of this study was to determine the chemical and physical characteristics of seven biochar derived from different biomass wastes - rice husk, corn cob, empty oil palm fruit bunch, bagasse, and sawdust of albazia (Albizzia falcataria), maesopsis (Maesopsis eminii), and mahogany (Swietenia macrophylla) at two low-pyrolysis temperatures (250 and 350 oC). The results showed that the percentage of biochar yield decreased at higher temperature level. However, the increased thermal decomposition of plant biomass wastes (at 350 oC) resulted in higher pH, as well as ash, C, N content of the biochar; but it did not significantly affect nutrient availability. Biochar from wood waste had more C and Ca content. Biochar from rice husk produced the highest ash content, while biochar from empty oil palm fruit bunch yielded the highest pH value, and possessed more nutrients than all the others. Increasing pyrolysis temperature from 250 to 350 oC resulted in greater biochar surface area and total pore volume but produced smaller average pore radius.